Antifungal Activity of Arginine-Based Surfactants - Fait, María Elisa (2018)
Background: Amino acid based surfactants constitute an important class of surface active biomolecules showing remarkable biocompatible properties. Antimicrobial activity is one of the most remarkable biological properties of this kind of surfactants, which have been widely studied against a broad spectrum of microorganisms. However, the antifungal activity of this kind of compound has been less well investigated. The aim of this work is the study of the antifungal activity of two novel argininebased surfactants (N -benzoyl-arginine decylamide, Bz-Arg-NHC10 and N -benzoyl-arginine dodecylamide, Bz-Arg-NHC12), obtained by an enzymatic strategy, against phytopathogenic filamentous fungi and dermatophyte strains. Methods: Four phytopathogenic fungi (Fusarium oxysporum, Fusarium solani, Colletotrichum gloeosporioides and Colletotrichum lindemuthianum) and two human pathogenic fungi (dermatophytes Trichophyton rubrum and Trichophyton mentagrophytes) were tested. Inhibition of vegetative growth and conidia germination was investigated for the phytopathogenic fungi. In order to elucidate the possible mechanism of biocide action, membrane integrity, as well as the production of reactive oxygen species (ROS) were evaluated. Additionally, the inhibition of germination of dermatophyte microconidia due to both arginine-based surfactants was studied. Minimum inhibitory concentration, as well as the concentration that inhibits 50% of germination were determined for both compounds and both fungal strains. Results: For the vegetative growth of phytopathogenic fungi, the most potent arginine-based compound was Bz-Arg-NHC10. All the tested compounds interfered with the conidia development of the studied species. Investigation of the possible mechanism of toxicity towards phytopathogenic fungi indicated direct damage of the plasma membrane and production of ROS. For the two strains of dermatophyte fungi tested, all the proved compounds showed similar fungistatic efficacy. Conclusion: Bz-Arg-NHC10 and Bz-Arg-NHC12 were demonstrated to have broad biocidal ability against the proliferative vegetative form and the asexual reproductive conidia. Results suggest that both membrane permeabilization and induction of oxidative stress are part of the antifungal mechanisms involved in the interruption of normal conidia development by Bz-Arg-NHCn, leading to cell death.